Sorting Through the Lost and Found: Are Patient Perceptions of Engagement in Care Consistent With Standard Continuum of Care Measures?. (1st May 2015) - Castel, Amanda D.; Tang, Wenze; Peterson, James; Mikre, Meriam; Parenti, David; Elion, Richard; Wood, Angela; Kuo, Irene; Willis, Sarah; Allen, Sean; Kulie, Paige; Ikwuemesi, Ifeoma; et al.
Abstract : Background: Indicators for determining one's status on the HIV care continuum are often measured using clinical and surveillance data but do not typically assess patient perspectives. We assessed patient-reported care status along the care continuum and whether it differed from medical records and surveillance data. Methods: Between June 2013 and October 2014, a convenience sample of clinic-attending HIV-infected persons was surveyed regarding care-seeking behaviors and self-perceived status along the care continuum. Participant responses were matched to DC Department of Health surveillance data and clinic records. Participants' care patterns were classified using Health Resources Services Administration–defined care status: in care (IC), sporadic care (SC), or out of care (OOC). Semistructured qualitative interviews were analyzed using an open coding process to elucidate relevant themes regarding participants' perceptions of engagement in care. Results: Of 169 participants, most were male participants (64%) and black (72%), with a mean age of 50.7 years. Using self-reported visit patterns, 115 participants (68%) were consistent with being IC, 33 (20%) SC, and 21 (12%) OOC. Among OOC participants, 52% perceived themselves to be fully engaged in HIV care. In the previous year, among OOC participants, 71% reported having a non–HIV-related medical visit and 90% reported current antiretroviral use. Qualitatively, most SC and OOC persons did not see their HIV providers regularly because they felt healthy. Conclusions: Participants' perceptions of HIV care engagement differed from actual care receipt as measured by surveillance and clinical records. Measures of care engagement may need to be reconsidered as persons not receiving regular HIV care maybe accessing other health care and HIV medications elsewhere.